Social context influences Toxoplasma gondii and Trichinella spp. infection in Alberta free-roaming wild pigs (Sus scrofa) - Kiera Middel; Hailey Strydhorst; Hannah McKenzie; Chunu Mainali; Darcy R. Visscher (PLoS ONE, 2025)
The increasing spread of wild pigs across Canada is concerning due to their potential role as reservoirs for zoonotic diseases, including trichinosis and toxoplasmosis. Trichinosis is caused by the parasitic nematode Trichinella spp. and can manifest clinically in humans. Likewise, the intracellular protozoan parasite Toxoplasma gondii is a significant global foodborne and waterborne parasite responsible for toxoplasmosis. Despite wild pigs being recognized globally as reservoirs for T. gondii and Trichinella spp., the status of wild pigs in Alberta remains undetermined. Wild pig diaphragms were collected as part of provincial control efforts between 2018–2024 from four Alberta counties. Meat juice was analyzed for antibodies against Trichinella spp. and T. gondii using commercial ELISA kits. We found that 27/252 pigs were positive for antibodies against T. gondii and 11/293 positive for antibodies against Trichinella spp., corresponding with the respective true prevalence of 15.3% (95% CrI: 9.6–22.7%) and 3.8% (95% CrI: 1.8–6.5%) based on Bayesian analysis using reported test sensitivity and specificity. We found a difference in true prevalence of antibodies against Trichinella spp. between counties, and the prevalence of antibodies against Trichinella spp. and T. gondii was significantly higher in solitary wild pigs, suggesting social context of the individual is an important determinant of infection risk. These findings suggest that Alberta wild pigs function as Trichinella spp. and T. gondii reservoirs, underscoring the need for a One Health approach for managing Alberta’s invasive wild pigs.